Nanoscale and microscale phenomena : fundamentals and applications - Joshi, Yogesh M.; Khandekar, Sameer (Springer Tracts in Mechanical Engineering,, 2015)
The book is an outcome of research work in the areas of nanotechnology, interfacial science, nano- and micro-fluidics and manufacturing, soft matter, and transport phenomena at nano- and micro-scales. The contributing authors represent prominent research groups from Indian Institute of Technology Bombay, Indian Institute of Technology Kanpur and Indian Institute of Science, Bangalore. The book has 13 chapters and the entire work presented in the chapters is based on research carried out over past three years. The chapters are designed with number of coloured illustrations, figures and tables. The book will be highly beneficial to academicians as well as industrial professionals working in the mentioned areas.